Editorial: STAT‐4 polymorphism ‐ a tool to personalise clinical practice in chronic HBV infection. Issue 7 (23rd September 2018) - Bonacci, Martin; Lens, Sabela
Abstract : Linked Content This article is linked to El Sharkawy et al papers. To view these articles visit https://doi.org/10.1111/apt.14866 and https://doi.org/10.1111/apt.14940 .